Association between sarcopenia and sleep disorder in older patients with diabetes. Issue 5 (17th February 2019) - Ida, Satoshi; Kaneko, Ryutaro; Nagata, Hiroaki; Noguchi, Yoshinori; Araki, Yasuha; Nakai, Mari; Ito, Sho; Ishihara, Yuki; Imataka, Kanako; Murata, Kazuya
Abstract : Aim: In the present study, we aimed to examine the association between sarcopenia and sleep disorder in older patients with diabetes using the Japanese version of SARC‐F (SARC‐F‐J). Methods: Outpatients with diabetes (aged ≥65 years) at the Ise Red Cross Hospital were included in the present study. We used the Japanese version of the Pittsburgh Sleep Quality Index, which is a self‐administered questionnaire, to measure sleep disorder. To evaluate sarcopenia, we used SARC‐F‐J, a self‐administered questionnaire, comprising five items. For multiple logistic regression analysis, the dependent variable was sleep disorder and the explanatory variable was sarcopenia, and these were used for calculating the odds ratios of sarcopenia with regard to sleep disorder. Results: In total, 318 patients were included in this study (189 men and 129 women). The prevalence of sarcopenia was 22.5% and that of sleep disorder was 44.8%. Adjusted odds ratios of sarcopenia and sleep disorder were 6.04 in men (95% CI 1.71–21.36, P = 0.005) and 6.33 in women (95% CI 1.91–20.97, P = 0.003). Conclusions: We found a statistically significant association between sarcopenia and sleep disorder in older patients with diabetes using SARC‐F‐J. Therefore, older patients with diabetes should be cautioned regarding sleep disorder if they are diagnosed with sarcopenia.Geriatr Gerontol Int 2019; 19: 399–403 .